The Effect of Service Quality and Online Promotion on Customer Loyalty Through Customer Satisfaction at F3B Beauty House - Febrina Isra Hertiane; Hari Muharam; Agus Setyo Pranowo (PT. Maju Malaqbi Makkarana, 2026)
Customer loyalty is essential for the sustainability of aesthetic clinics, particularly amid increasing competition and the growing use of digital promotional channels. This study examines the effects of service quality and online promotion on customer loyalty, with customer satisfaction as a mediating variable at F3B Beauty House. A quantitative explanatory design with a cross-sectional survey approach was employed. Data were collected through an online questionnaire from 361 customers selected using purposive sampling. Eligible respondents were at least 18 years old, had completed at least two visits or transactions within the previous 12 months, and had been exposed to the clinic’s online promotions. The data were analyzed using partial least squares structural equation modeling. The results show that service quality and online promotion positively and significantly affect customer satisfaction and customer loyalty. Customer satisfaction also has a positive and significant effect on customer loyalty and demonstrates the largest practical effect. Furthermore, customer satisfaction partially mediates the effects of service quality and online promotion on customer loyalty. The model explains 66.9% of the variance in customer satisfaction and 68.3% of the variance in customer loyalty. These findings emphasize the importance of integrating consistent service quality, interactive online promotion, and satisfactory customer experiences to strengthen sustainable customer loyalty.